Nature reserve foundation of Skibovy Gorgany: structure and prospects of optimization (Ukrainian Carpathians) - Brusak , V. P.; Popyk , D. I. (Man and Environment. Issues of Neoecology, 2022)
Purpose. Revealing of the structure and features of the nature reserve fund (NRF) of Skibovy Gorgany and the prospects for its optimization. Methods. Field, processing of environmental services` fund materials, statistical and geospatial analysis, cartographic. Results. The fund materials of environmental services have been processed, the structure has been established and specific features of Skibovy Gorgany nature reserve fund have been clarified. There are 190 objects of the nature reserve fund with total area of 62,961.3 hectares in Skibovy Gorgany. The structure of the NRF was analyzed by categories, area and number of protected objects, their level of importance and objects of protection. Brief description and a complete list of categories of the nature reserve fund are given. The list and characteristics of unique and valuable inanimate nature objects of Skibovy Gorgany as a kind of natural region of the Ukrainian Carpathians and within the nature reserve "Gorgany" are given. The problems of development are pointed out and the ways of improving the protection of valuable geomorphological objects by creating new objects and expanding the existing nature reserves of the Skibovy Gorgany NRF are suggested. Conclusions. There are few protected sites in Skibovy Gorgany, aiming to preserve valuable inanimate natural objects, especially geomorphological ones. Among the latter, within the Ukrainian Carpathians the following valuable objects should be identified: fields of stone placers and glacial boilers (сirque), large landslides and screes, rock outcrops, canyon-like areas of river valleys with rapids, mudflow cones. It could be proposed to create the Regional Landscape Park in the area of the Syvulyansky mountain range and the Rushchyna montane meadow with tract “Peklo” and the sources of the Bystritsa Solotvynska River.